Предмет: Математика,
автор: denvic11
(1/(1-ctg^2B))+(1/(tg^2B-1))=(1/(sin^2B-cos^2B))
Ответы
Автор ответа:
0
(sina+cosa)^2=1/3^2
(sina)^2+2sinacosa+ (cosa)^2=1/9 (sina)^2+(cosa)^2=1 2sinacosa=sin2a
1+sin2a=1/9
sin2a=-8/9
Вроде так...))))
(sina)^2+2sinacosa+ (cosa)^2=1/9 (sina)^2+(cosa)^2=1 2sinacosa=sin2a
1+sin2a=1/9
sin2a=-8/9
Вроде так...))))
Похожие вопросы
Предмет: Русский язык,
автор: mksimpetrosov18
Предмет: История,
автор: kozakozlik0
Предмет: Русский язык,
автор: Milanakaaa67
Предмет: Информатика,
автор: 12345Dfend